DIPLOCHORY IN NORTHERN NIGERIA: YOU CAN’T PREDICT DISPERSAL OF SEED BY ITS FRUIT SIZE - ALIYU, BABALE; ABUBAKAR Z.A; MOHAMMED, ISMAIL; SAIDU, HARUNA; MUSA, ILIYA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2019)
Diplochory is well known to contribute to the regeneration of Neotropical forests, particularly in the context of frugivore decline. However, this phenomenon in Old World woodlands is virtually unknown. Here we contribute to our understanding of diplochory in woodland habitats experiencing frugivore loss by investigating for the first time the interaction of habitat and seed type on secondary dispersal by rodents. Moreover, our study combines information on degraded woodland (habitat), organism (Scatterhoarding rodent) and large seeded species dispersed by frugivores. We established seed ‘dumps’ to simulate frugivore dispersed seed in each of three woodland - habitats Yankari Game Reserve, Kanawa woodland, and Nafada degraded woodland. We quantify how degradation and seed size interact to affect the balance between predation and dispersal. We distinguish between burial and cached seed. Bayesian statistics was used to compare predation rates and proportion of seed i) buried and ii) cached in each habitat, large and small seeded species were used. Infra-red cameras were established to identify predators and/or seed dispersers. Seed fate differed markedly among habitats. Seed predation rates were highest in degraded woodland habitats than in Reserve habitat (YGR->NFD) P = 0.94, however, the probability of being predated was higher for the large seeded species than for the small seeded species. The probability of scatterhoarded seed being buried was markedly higher than being cached. Almost all seeds were predated and dispersed by the African pouched rat, Cricetomys gambianus. In this study we demonstrate the importance of diplochory in Old World woodlands and quantify the role of scatterhoarding with respect to habitat and seed size in the context of habitat degradation. Seed predation is markedly higher in degraded habitats particularly for small seeded species. Seed burial is more common than caching across all habitats and dispersal is markedly higher in Reserve than disturbed or degraded woodland. Our findings should stimulate a new area of research into Old World plant-animal mutualisms.